1979
DOI: 10.1002/polc.5070660144
|View full text |Cite
|
Sign up to set email alerts
|

The biologic activity of polyanions: Past history and new prospectives

Abstract: SYNOPSISThe toxicology of synthetic polyanions relates to molecular weight. This developed from experience with pyran copolymer (divinyl ether maleic anhydride copolymer), which was tested clinically as an antitumor agent and found to be too toxic for continued clinical trial. Synthetic polyanions of low molecular weight are potent stimuli to macrophage phagocytic function and possess antitumor activity. Increased host resistance to pathogens including bacteria, fungi, viruses, and trypanosomes is seen. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 161 publications
0
4
0
Order By: Relevance
“…An attractive candidate for this approach is the copolymer of divinyl ether with maleic anhydride widely known as DIVEMA. This remarkable polymer extensively studied in the 70s and 80s exhibits the broad spectrum of biological activities such as induction of biological response to tumors, antiviral and antibacterial activity explained most probably by induction of interferon production and/or macrophage activation [11,12]. Due to this per se activity, DIVEMA became one of the rst synthetic polymers clinically tested as the anticancer agent; however, despite the antitumor activity evidenced in numerous preclinical studies, no signi cant effect was observed in humans [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…An attractive candidate for this approach is the copolymer of divinyl ether with maleic anhydride widely known as DIVEMA. This remarkable polymer extensively studied in the 70s and 80s exhibits the broad spectrum of biological activities such as induction of biological response to tumors, antiviral and antibacterial activity explained most probably by induction of interferon production and/or macrophage activation [11,12]. Due to this per se activity, DIVEMA became one of the rst synthetic polymers clinically tested as the anticancer agent; however, despite the antitumor activity evidenced in numerous preclinical studies, no signi cant effect was observed in humans [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Polyelectrolytes are widely known for their immunostimulatory properties. [5][6][7] We recently introduced a novel adjuvant, termed SPA09, based on high molecular weight linear polyacrylate readily available and easy to formulate with vaccine antigens. 8 In previous studies in mice, SPA09 was found to work as a strong T H 1-type adjuvant when tested with various types of antigens including the recombinant glycoprotein CMV-gB and a Staphylococcus aureus polysaccharide conjugate (patent WO2017218819A1).…”
Section: Introductionmentioning
confidence: 99%
“…Polyelectrolytes are widely known for their immunostimulatory properties. 5–7 We recently introduced a novel polyelectrolyte adjuvant, termed SPA09, based on high molecular weight linear polyacrylate (PAA) readily available and easy to formulate with vaccine antigens. 8 …”
Section: Introductionmentioning
confidence: 99%
“…There is definitely a need for additional adjuvants that could be safely used in humans, would be easy to source and to formulate with a wide range of antigens and would be broadly applicable to a wide range of vaccines. In this regard, different studies indicated that polyacrylates (PAAs) in different forms and formats were safe and biocompatible and adjuvant active within a range of polymer sizes, doses, formulations and routes of administration compatible with vaccination ( Coucke et al, 2009 ; Cranage et al, 2011 ; De Clercq, 2010 ; Diamantstein et al, 1971 ; Gartlan et al, 2016 ; Hicks et al, 1989 ; Krashias et al, 2010 ; Kreuter and Haenzel, 1978 ; Mustafaev, 1996 ; Parker et al, 2009 ; Powell et al, 2015 ; Regelson, 1979 ; Wegmann et al, 2015 ; Zondlo Fiume, 2002 ). Among the adjuvant-active PAAs, one can find plain PAAs ( Diamantstein et al, 1971 ; Hilgers et al, 1998a ), PAA dendrimers ( Zaman et al, 2010 , 2011 ), PAA alkyl esters ( Hilgers et al, 2000 , 1998b ; Tifrea et al, 2011 ) and the crosslinked PAAs ( i.e.…”
Section: Introductionmentioning
confidence: 99%